(3eHGOF GdEOGQI eY GdJQcjR Ydi EOGQI GdGYeGds - (3Ndjd eMeO MSf(B, (3GdTeGZs ((3YeGf(B:s (3OGQ GdeSjQI ddfTQ(B,s, 1999)
(3WHjYI GdEOGQI hJWhQ acQgG hHjFJgG(B- (3GdJNWjW hGJNGP GdbQGQ(B- (3GdJfXje(B- (3GdbjGOI hGdJMajR(B- (3GdQbGHI(B- (3EOGQI CfTWI GdefTCIs
Keywords: (3EOGQI GdCYeGds; (3GdEOGQIs